1998
DOI: 10.1016/s0029-7844(98)00105-7
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Imbalance in Preeclampsia: Evidence for Increased Sympathetic Tone in Response to the Supine-Pressor Test

Abstract: Third-trimester pregnancy is characterized by sympathetic overactivity. When complicated by preeclampsia, sympathetic overreactivity to cardiovascular reflex testing is observed. Our data support the notion that the pathophysiologic phenomena that characterize preeclampsia are mediated not only by circulating or locally acting vasoactive substances, but also, at least in part, by an increase in sympathetic nervous tone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 12 publications
0
35
0
Order By: Relevance
“…Other studies have concluded that both sympathetic and vagal responses are increased in pre-eclampsia [29]. Pre-eclamptic women have an autonomic imbalance associated with an increase in sympathetic nervous tone, increased heart rate, and hypertension as compared to normal pregnant women [30,31].…”
Section: Obstructive Sleep Apnea Associated With Endothelial Functionmentioning
confidence: 98%
“…Other studies have concluded that both sympathetic and vagal responses are increased in pre-eclampsia [29]. Pre-eclamptic women have an autonomic imbalance associated with an increase in sympathetic nervous tone, increased heart rate, and hypertension as compared to normal pregnant women [30,31].…”
Section: Obstructive Sleep Apnea Associated With Endothelial Functionmentioning
confidence: 98%
“…This showed a pronounced increase in power in the very low-frequency range of heart rate variability, suggesting a marked increase in sympathetic tone. 172 The urinary excretion of both prostaglandin 6-keto F 1␣ and kallikrein is reduced long before clinical signs of the disease are apparent (eg, Fitzgerald et al, 1987 73 ;Millar et al, 1996 162 ; Mills et al, 1999 173 ), perhaps again reflecting early endothelial damage. There is considerable interest in the possibility of decreased endothelial NO synthesis contributing to the vasoconstriction of PE.…”
Section: The Cardiovascular Systemmentioning
confidence: 99%
“…63 Women who develop severe preeclampsia, especially early-onset, have a higher rate of deaths attributable to CVD as well as an increased risk of having family members who have had early-onset CVD of any type. 15,21,54,62 Although this study was small, specifically preventing us from exploring the relationship and statistical significance of first-and second-generational FH for HTN, MI, and stroke, we were able to identify several known physiologic clinical precursors to both preeclampsia and ischemic CVD, supporting the hypothesis that there is a nonpregnancy phenotype that exists in young women who have an FH of these cardiovascular events. This phenotype likely contributes to the ''pregnancy as a stress-test'' hypothesis, whereby preeclampsia unmasks preexisting physiologic characteristics that predispose to preeclampsia and future CVD risk.…”
Section: Discussionmentioning
confidence: 56%